Legal Analysis of Unfair Competition Between Notaries in The Perspective of The Code of Ethics of The Indonesian Notaries Association - Malidu, Risma Safitri; Suwondo, Denny (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. This study aims to determine and analyze the regulation of the notary's code of ethics, to determine and analyze the legal analysis of unfair competition of notaries in the perspective of the Indonesian Notary Association's code of ethics. The approach method in this study is the statute approach. This type of research is normative research. The type and source of data in this study are secondary data obtained through literature studies. The analysis in this study is perspective. The results of the study indicate that the regulation of the notary's code of ethics in Indonesia has a crucial role in maintaining the integrity and credibility of the notary profession as a public official who prepares authentic deeds. This code of ethics aims to ensure that every notary's action is based on the principles of professionalism, objectivity, and the interests of society and the state. Although there are regulations governing the code of ethics in the Notary Law and Government Regulations, its implementation still faces challenges, especially related to ethical violations in the field. Therefore, supervision and enforcement of the code of ethics require an active role from external institutions such as the Notary Supervisory Board, in addition to the internal mechanisms of the notary professional organization. The importance of an effective code of ethics also contributes to the creation of more transparent, accountable, and trustworthy public services. This will strengthen the legal position of notarial deeds in the Indonesian legal system. Referring to existing provisions, especially regarding the minimum honorarium for notaries set by the Indonesian Notary Association (INI) for the Southeast Sulawesi Region, regional administrators have the authority to file a lawsuit for breach of contract against notaries who charge an honorarium below the agreed standard. Based on Article 1655 of the Civil Code, administrators can act in court as either plaintiffs or defendants.Keywords: Code of Ethics; Unfair Competition; Notary